Teacher-Student Relationship in Obstetrics and Gynaecology Department in Different Medical Colleges of Bangladesh - Taslima, Kazi; Kabir Talukder, Md Humayun (Medicine Today, 2021)
Introduction: Teacher-student relationship is very important element in education to enhance the effectiveness of teaching and learning process. There are multiple factors affecting this relation. If we analyze these factors and take measures to improve these, there will be better relation; and teaching learning will be improved. Materials & Methods: This descriptive type of cross-sectional study was carried out in obstetrics and gynaecology department of selected medical colleges of Bangladesh. Five government & three non-government medical colleges were selected purposively situated both in Dhaka and outside during the period of July 2017 to June 2018. Total 170 students and 30 teachers were responded through self-administered semi-structured questionnaire with five points Likert scale. 20 teachers were responded through in-depth interview schedule. Quantitative data analyzed by SPSS version 19. Qualitative data analyzed manually. Results: Study revealed that multiple factors were related to the relation among medical teachers and students. Mutual respect, empathy, Good listening skill, mutual respect, sharing expectation, self-disclosure, awareness about own role are the most important influencing factors in this relation (mean score >4). Use of drugs/tobacco, speech difficulty, love affair of students, negatively affect communication. Study also revealed barriers of relation fear and shyness, language barrier and discrimination of students by the teachers. Friendly relationship, open minded behavior, student- teachers cooperation, open discussion, morality and religious practice, motivation of by teachers, understanding each other’s, avoidance of student’s politics, responsibility of students & teachers, teachers training with reduced workload have great impact on removing these barriers. Conclusion: Addressing these issues at all possible levels, proper measures should be taken to improve relation among teachers and students; so that teaching learning process can be enhanced and ultimate goal of medical education can be achieved. Medicine Today 2021 Vol.33(2): 165-168